2017
DOI: 10.1155/2017/5706193
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Chronic Intermittent Hypobaric Hypoxia Pretreatment against Aplastic Anemia through Improving the Adhesiveness and Stress of Mesenchymal Stem Cells in Rats

Abstract: Aplastic anemia (AA) is a common malignant blood disease, and chronic intermittent hypobaric hypoxia (CIHH) has a beneficial effect against different diseases. The aim of the present study was to investigate the protective effect of CIHH against AA and underlying mechanisms. 5-Fluorouracil and busulfan treatment induced AA model in rats with reduction of hematological parameters and bone marrow tissue injury and decrease of the colony numbers of progenitor cells. CIHH pretreatment significantly reduced the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Our previous studies demonstrated that CIHH reduced the hematopoietic dysfunction and antagonized anemia by increasing the serum positive hematopoietic regulatory factor Epo. But it does not clarify the effects and mechanisms of CIHH on hepcidin and iron metabolism in obese rats [ 20 ]. In this study, we found that in obese rats the level of Epo was significantly decreased and hepcidin was increased, and CIHH effectively increased Epo and downregulated hepcidin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies demonstrated that CIHH reduced the hematopoietic dysfunction and antagonized anemia by increasing the serum positive hematopoietic regulatory factor Epo. But it does not clarify the effects and mechanisms of CIHH on hepcidin and iron metabolism in obese rats [ 20 ]. In this study, we found that in obese rats the level of Epo was significantly decreased and hepcidin was increased, and CIHH effectively increased Epo and downregulated hepcidin.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has demonstrated the benefits of chronic intermittent hypobaric hypoxia (CIHH) on multiple organs of the body such as heart, brain, liver, and kidney [ 15 18 ], including regulating immune system, anti-collagen-induced arthritis [ 19 ], antihypertensive activity [ 15 ], and improving dyslipidemia and glucose tolerance in type 2 diabetes [ 16 ] . Recently, it was reported that CIHH had an anti- aplastic anemia eect through improving the adhesiveness and stress of mesenchymal stem cells [ 20 ], and a modulating effect on brain iron homeostasis in rats [ 18 ] . Accordingly we proposed the hypothesis that CIHH may ameliorate the abnormal iron metabolism in obesity.…”
Section: Introductionmentioning
confidence: 99%